Evidence for global cooling in the Late Cretaceous - C. Linnert; S. A. Robinson; J. A. Lees; P. R. Bown; I. Pérez Rodríguez; K. Littler; J. A. Arz; E. E. Russell; M.R. Petrizzo; F. Falzoni (Nature Communications, 2014)
The Late Cretaceous â ̃ greenhouseâ ™ world witnessed a transition from one of the warmest climates of the past 140 million years to cooler conditions, yet still without significant continental ice. Low-latitude sea surface temperature (SST) records are a vital piece of evidence required to unravel the cause of Late Cretaceous cooling, but high-quality data remain illusive. Here, using an organic geochemical palaeothermometer (TEX 86), we present a record of SSTs for the Campanian-Maastrichtian interval (∼83-66 Ma) from hemipelagic sediments deposited on the western North Atlantic shelf. Our record reveals that the North Atlantic at 35 ° N was relatively warm in the earliest Campanian, with maximum SSTs of ∼35 ° C, but experienced significant cooling (∼7 ° C) after this to <∼28 ° C during the Maastrichtian. The overall stratigraphic trend is remarkably similar to records of high-latitude SSTs and bottom-water temperatures, suggesting that the cooling pattern was global rather than regional and, therefore, driven predominantly by declining atmospheric pCO 2 levels.